The Need for an Interactive Cell Biology Textbook Based on Case Studies by Integrating QR Codes - Harlis; Dara Mutiara Aswan (LPPM Undiksha, 2024)
Cell Biology is a course whose material is abstract because it cannot be observed with the naked eye. The problem in learning Cell Biology is that no reference books can make abstract material more real to facilitate students' understanding. This research aims to analyze students' needs for Case Study-based interactive Cell Biology textbooks by integrating QR Codes. This research is quantitative and descriptive. The subjects in this research were Biology Education students. Data was obtained through interviews, observations, and questionnaires. Data were analyzed using quantitative descriptive methods. Based on data analysis, 67.6% of students stated that they could only imagine the structures and processes in cells, and 86.5% needed help understanding Cell Biology material. The results of the data analysis also show that all samples agreed to develop teaching materials that integrate QR codes connected to various videos or literature. Based on these results, an interactive cell biology textbook based on case studies needs to be created by further integrating QR codes.